Teori Belajar Humanistik dan Penerapannya dalam Pembelajaran Sejarah - Hastuti, Hera; Neviyarni, Neviyarni; Wela, Rasmila (Jurnal Kronologi, 2025)
Humanistic learning theory places the individual at the center of the educational process, focusing on developing personal potential through the fulfillment of basic human needs, as outlined by Abraham Maslow and Carl Rogers. This approach emphasizes the importance of a supportive environment, respect for student independence, and the teacher's role as a facilitator in creating a learning space that focuses on students' emotional and social well-being. In the context of history learning, the application of this theory offers opportunities to create more meaningful and life-connected learning experiences for students, enabling them to develop critical and reflective thinking skills. Through experiential learning, empowering students to determine learning goals, and integrating humanitarian values, humanistic theory can help enrich historical understanding beyond cognitive, affective, and social learning. This study aims to explore the basic principles of humanistic learning theory and apply these principles to history learning, in order to increase student engagement and achieve more holistic and sustainable learning. These findings are expected to provide insights for educators in creating more inclusive history learning that is based on student self-development.